Experimental investigation on the correlation between nano-fluid characteristics and thermal properties of Al2O3 nano-particles dispersed in ethylene glycol–water mixture. (March 2016) - Xu, Jinghai; Bandyopadhyay, Krisanu; Jung, Dohoy
Highlights: Multiple correlations between nano-fluid characteristics and thermal properties. Nano-fluid benefit was maximized through the proper nano-fluid preparation. Al2 O3 nanoparticle showed a high thermal conductivity enhancement in ethylene glycol–distilled water mixture. Abstract: This paper presents a multi-parameter investigation of Al2 O3 nano-particles dispersed in distilled water, ethylene glycol and ethylene glycol–distilled water mixture (50/50 vol.%). The nano-fluid samples were prepared with ultrasonic processing with particle concentration up to 9 wt.%. Samples were characterized by transmission electron microscope imaging, particle surface charge (zeta potential), particle aggregate size, light absorbance and pH. The thermal conductivity and viscosity of the nano-fluid samples were measured. 10.9% enhancement in thermal conductivity was observed in ethylene glycol–distilled water mixture based nano-fluid with 5 wt.% Al2 O3 nano-particle loading. The results show multiple-perspective correlations between nano-fluid characteristics and thermal properties. The findings are summarized as follows. Combined effect of base fluid viscosity and particle surface charge determines the degree of nano-particle aggregation. Higher enhancement in thermal conductivity is observed with moderate particle aggregation, while either light or heavy aggregation lowers the enhancement. The ethylene glycol–water mixture based nano-fluids show overall higher thermal conductivity enhancement than the distilled water and ethylene glycol based nano-fluids. The degradation of nano-fluid thermal conductivity enhancement over time is found to be related to the gravity-driven particle sedimentation. Nano-fluids containing larger particle aggregates show higher viscosity augmentation. However, the extent of viscosity augmentation is not proportional to the extent of particle aggregation.